Kant's moral and legal philosophy / edited by Karl Ameriks, Otfried Höffe ; translated by Nicholas Walker. - Ameriks, Karl, 1947-; Höffe, Otfried; Walker, Nicholas, 1954- (German philosophical tradition., 2009)
This volume brings to English readers the finest postwar German-language scholarship on Kant's moral and legal philosophy. Examining Kant's relation to predecessors such as Hutcheson, Wolff, and Baumgarten, it clarifies the central issues in each of Kant's major works in practical philosophy, including The Groundwork of the Metaphysics of Morals, The Critique of Practical Reason, and The Metaphysics of Morals. It also examines the relation of Kant's philosophy to politics. Collectively, the essays in this volume provide English readers with a direct view of how leading German philosophers are now regarding Kant's revolutionary practical philosophy, one of the outstanding achievements of German thought.